Analiza uporabnosti različnih metod za določanje vertikalnih mikropomikov objektov - Kovačič, Boštjan (Geodetski vestnik, 2001)
The paper presents the methods for controlling vertical displacements of a reinforced concrete slab. To take the measuremants we used geodetical instruments (level, total station and laser level) as well as non-geodetical instruments (inductive transducers). The theoretical displacements at the crack were calculated in accordance with European regulations for reinforced and prestressed concrete.
Keywords: geodesy; geodetske metode; geodezija; meritve